2020
DOI: 10.1055/s-0040-1710148
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Different Chemical Agents and Herbal Products in Disinfecting Gutta-Percha Cones: An In Vitro Study

Abstract: Introduction The main aim of this study was to compare and evaluate different chemical agents and herbal products in disinfecting gutta-percha (GP) cones through an in vitro study. Materials and Methods For this study, 160 GP cones were taken in test tubes, which were contaminated with Enterococcus faecalis inocula, prepared by dissolving it in Brain Heart Infusion (BHI) broth. The GP cones were then taken from the test tubes and dried on Whatman filter paper no. 1 and were divided into four groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…In the present study Lemon grass oil had shown excellent disinfection of gutta-percha cones followed by PanchaTulasi and ozonated olive oil. [8][9][10][11][12]…”
Section: Discussionmentioning
confidence: 99%
“…In the present study Lemon grass oil had shown excellent disinfection of gutta-percha cones followed by PanchaTulasi and ozonated olive oil. [8][9][10][11][12]…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar peneliti menggunakan media brain heart infusion (BHI) sebagai media dalam uji dekontaminasi gutaperca. 9,11,16 Berbeda dengan penelitian Natasha et al pada tahun 2015 yang memilih menggunakan nutrient broth sebagai media pada uji dekontaminasi gutaperca ini. 10 Proses selanjutnya adalah inkubasi cawan petri dan tube yang sudah berisi media.…”
Section: Metodeunclassified
“…Temperatur dan lama inkubasi dapat menjadi faktor yang mempengaruhi pertumbuhan bakteri. Sampel penelitian Bansal et al pada tahun 2020 diinkubasi selama 72 jam di suhu 37 o C. 11 Berbeda dengan penelitian Shenoi et al pada tahun 2014 yang melakukan inkubasi selama 24 jam di suhu 37 o C. 9 Lama dan suhu inkubasi serupa juga dilakukan oleh sebagian besar peneliti lainnya, yaitu selama 24 jam di suhu 37 o C. 10,12,13,16 Durasi inkubasi yang berbeda juga ditemukan pada penelitian Mukka et al pada tahun 2017 dan Jyothsna et al pada tahun 2020, kedua peneliti ini melakukan inkubasi sampel selama 48 jam pada suhu 37 o C. 7,14 Setelah proses inkubasi selesai, kemampuan antibakteri suatu bahan atau zat dapat dinilai dengan cara mengukur diameter zona hambat ataupun menghitung colony forming unit (CFU) yang terbentuk pada media tersebut. Shailja et al pada tahun 2018 menilai efektivitas antibakteri Aloe vera dengan cara mengukur diameter zona hambat menggunakan jangka sorong.…”
Section: Metodeunclassified